KARAKTERISTIK, MOTIVASI, DAN SIKAP WISATAWAN MANCANEGARA MENGGUNAKAN PAKET WISATA MOBIL VW SAFARI DI UBUD VW TOUR - Prasetyo, Kadek Nova; Suardana, I Wayan; Suwena, I Ketut (Jurnal IPTA (Industri Perjalanan Wisata); Vol 10 No 1 (2022): Jurnal IPTA (July 2022), 2022)
Uniqueness of the VW Safari tour car is able to attract foreign tourists to use tour package services in Bali, and in this study focuses on the characteristics, motivations, and attitudes of foreign tourists who use the VW Safari car tour package services in Ubud VW Tour. . The sampling technique in this study used purposive sampling technique, and data collection used observation, interviews, and distributing questionnaires with a 5-point Likert scale model with the aim of being given to 105 foreign tourists as respondents. The results of the study show that foreign tourists who travel the most using the VW Safari tour car package services come from Australia with a vulnerable age of 31-45 years, male, work as private employees, and have master's education (S2). Based on the travel destination of foreign tourists, most of them stated that the purpose of their trip was to travel/recreation and stated that they had more trust in the travel agency in their travels and this was the first time they used this service. Ubud VW Tour, spends IDR 2,500,000 – IDR 3,500,000, and is accompanied by family during the tour. Rational motivation gets an average score of 4.32 (strongly agree), then for emotional motivation gets an average score of 4.36 (strongly agree). Foreign tourists who use the Ubud VW Tour tour package have a good attitude/agree with a score of 4.34. This research is expected to be used as a reference for managers to continue to improve service quality in order to maintain tourist loyalty, and continue to develop the promotion of Ubud VW Tour services by utilizing current technological sophistication.